1992
DOI: 10.1557/jmr.1992.1618
|View full text |Cite
|
Sign up to set email alerts
|

Ion-assisted pulsed laser deposition of cubic BN films on Si (001) substrates

Abstract: We report on oriented and adherent cubic BN films grown on (001) faces of silicon using the method of ion-assisted pulsed laser deposition. The structure of the films is cubic zinc-blende with a lattice constant of 3.62 A, as determined by infrared absorption and transmission electron microscopy. The films were found to be poly crystalline, and oriented with the cubic BN [110] axis parallel to the Si [001] direction.In this work we report the successful growth of oriented, adherent, cubic BN films. The films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(4 citation statements)
references
References 6 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Recently, considerable efforts have been made in the synthesis of c-BN thin films using a variety of ion-beam-assisted processes [3][4][5][6][7][8][9][10] and several plasma-, ion-, and laser-assisted chemical vapor deposition methods. [11][12][13] These investigations have established that the c-BN formation requires an initial sp 2 -bonded boron nitride layer ͑amorphous and tur-bostratic͒ grown onto the substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considerable efforts have been made in the synthesis of c-BN thin films using a variety of ion-beam-assisted processes [3][4][5][6][7][8][9][10] and several plasma-, ion-, and laser-assisted chemical vapor deposition methods. [11][12][13] These investigations have established that the c-BN formation requires an initial sp 2 -bonded boron nitride layer ͑amorphous and tur-bostratic͒ grown onto the substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…The three BN films used in this study were produced by ion-assisted pulsed laser deposition onto heated silicon substrates, as detailed previously. [6] Deposition conditions are summarized in Table 1. Infrared transmission measurements (not shown) on these films revealed absorption at wavelengths characteristic of both the cubic and hexagonal phases, allowing an estimate of their volume fraction.…”
Section: Methodsmentioning
confidence: 99%
“…4) c-BN is attractive to researchers both scientifically and technologically because of its unique features. Since the early 1960's when c-BN was first synthesized by a highpressure and high-temperature method, 5) diverse works have been carried out to synthesize c-BN in the thin-film form using the techniques of ion plating, 6) ion beam assisted deposition (IBAD), 7,8) ion assisted laser ablation, 9,10) magnetron sputtering 11,12) and plasma enhanced chemical vapour deposition (PCVD). 13,14) In almost all references reporting the successful synthesis of a c-BN film, it is found that energetic sure of 1 × 10 −6 Torr by a turbomolecular pump (TMP), then filled with a mixture of Ar and N 2 gases to a working pressure of 4.0 × 10 −3 Torr.…”
Section: Introductionmentioning
confidence: 99%